Titan's Variable Ionosphere During the T118 and T119 Cassini Flybys. Issue 17 (6th September 2018) - Edberg, N. J. T.; Vigren, E.; Snowden, D.; Regoli, L. H.; Shebanits, O.; Wahlund, J.‐E.; Andrews, D. J.; Bertucci, C.; Cui, J.
Abstract: We report on unusual dynamics in Titan's ionosphere as a significant difference in ionospheric electron density is observed between the T118 and T119 Cassini nightside flybys. Two distinct nightside electron density peaks were present during T118, at 1, 150 and 1, 200 km, and the lowest density ever observed in Titan's ionosphere at altitudes 1, 000–1, 350 km was during T118. These flybys were quite similar in geometry, Saturn local time, neutral density, extreme ultraviolet flux, and ambient magnetic field conditions. Despite this, the Radio and Plasma Waves/Langmuir Probe measured a density difference up to a factor of 6 between the passes. The overall difference was present and similar during both inbound and outbound legs. By ruling out other factors, we suggest that an exceptionally low rate of particle impact ionization in combination with dynamics in the ionosphere is the explanation for the observations. Plain Language Summary: Using the Cassini satellite in orbit around Saturn, we make measurements during two close passes of the moon Titan. We observe how the electron density in the uppermost part of the moon's atmosphere—the ionosphere—changes drastically from one pass to the next. We also observe unexpectedly high peaks of electron density in a specific altitude range during the first pass. The findings are attributed to low influx of charged particles from Saturn's magnetosphere as well as to increased dynamics of the plasma in the ionosphere. The study emphasizes the complexity of the physical process at play at the moon and aims at gaining further understanding of this environment. Key Points: Large difference in ionospheric electron density is seen between T118 and T119 despite similar geometry The lowest density ever observed in the altitude range 1, 000‐1, 350 km in Titan's nightside ionosphere was during T118 Low fluxes of impact ionizing particles and ionospheric dynamics is suggested as the most probable explanation